Graeber, D. (2018). Bullshit jobs: A theory. New York, NY: Simon and Schuster. (Journal of Applied Learning and Teaching, 2018)
Graeber’s book is based on his 2013 essay “On the Phenomenon of Bullshit Jobs” that caused an internet sensation, and within weeks, was translated into more than a dozen languages. The essay and its easily-relatable title hit a raw nerve and images of people looking busy, but secretly checking their social media accounts, immediately came to mind. In 2015, an anonymous group plastered the London Underground with quotations from the essay. Graeber conducted substantial qualitative research that enriches the text with many quotable testimonies and quite a few great stories. He analysed more than 250 thoughtful and detailed responses resulting from a Twitter request and also as a response to the original essay, and set up an email account doihaveabsjoborwhat@gmail.com (and also downloaded 124 descriptions people offered about their jobs in online discussions of his essay). But at the risk of stating the obvious, Graeber’s is an unabashedly polemical work. His important book is about a “neglected aspect of the world of work” that constitutes “a real social problem” (146) – “one that most people don’t even acknowledge exists” (270).